Letter to Jane Tolmach from John V. Tunney - John V. Tunney:::::: (1969)
In this October 24, 1969 letter, Congressman John V. Tunney sends Jane Tolmach the proposed guidelines of the McGovern Commission on Party Structure and Delegate Selection and invites her comments before the November 3 deadline. He expresses his view that California's convention delegation should fairly reflect differing voter viewpoints and outlines his compromise proposal to retain the winner-take-all primary unless no slate receives over 50%, in which case delegates would be allocated proportionally. Tunney urges support for reforms ensuring full and open participation in party processes to prevent conflicts like those seen in Chicago.